PELAKSANAAN JUAL BELI TANAH YANG BELUM BERSERTIFIKAT DI DENPASAR - Wijaya, I Gusti Ngurah Hadi Indrawan; Wiryawan, I Wayan; westra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
According to the laws of regulation base agrarian specifics, number law 5 year 1960 that the right evidence above a land in Indonesia is certificate of land right evidence. In the society, the fact that purchase and sale on land without certificate which is only base on Pipil / ground tax payment evidence still happen. Pipil that is ground tax payment Evidence only be tax voucher on soil. Whereas, certificate is strong proof about proprietary rights of land. Thereby, in this situation can cause a lawsuit of proprietary rights above a same land area. The method that used empirical juridical a approaches that done to analyze about as far as where a regulation/ legislation or law that operative effectively.
Keywords: sale, purchase, certificate, Pipil.